Issue Information TOC. Issue 2 (19th June 2019) - Unknown
Abstract : Cover : Image shows an embryonic day 18.5 (E18.5) mouse embryo imaged with three‐dimensional iodine‐contrast micro‐computed tomography (microCT). The 3D volume and individual section views were rendered with CTVox (Bruker) and the final image was assembled in Photoshop CC (Adobe). See Hsu et al. (https://doi.org/10.1002/cpmo.63 ).